Te-doped perovskite NaTaO3 as a promising photocatalytic material for hydrogen production from water splitting driven by visible light. (November 2018) - Liu, Yu-Liang; Yang, Chuan-Lu; Wang, Mei-Shan; Ma, Xiao-Guang; Yi, You-Gen
Graphical abstract: Highlights: S, Se and Te-doped NaTaO3 is a promising material for photocatalytic water splitting. Enhanced absorption coefficient in the visible light range is identified for Te-doped NaTaO3 . Te-doped NaTaO3 exhibits higher electron and hole mobility than pristine NaTaO3 . Abstract: The photocatalytic hydrogen production from water splitting can be achieved by using the pristine NaTaO3 experimentally, but the reaction cannot be driven by the visible light because of the wide band gap of NaTaO3 . The present work focuses on tuning the photocatalytic performance of NaTaO3 into the visible light range by doping S, Se, and Te elements. The obvious decrease in band energy gaps ( E g s) and noticeable red-shift of the absorption edges are observed for the doped structures. The valence band maximum and conduction band minimum of the doped structures satisfy the requirement of the water splitting. Moreover, a significant enhancement of absorption coefficient in the visible light range is observed for the doped structure of Te@O. The calculated carrier mobility is used to evaluate the charge spatial separation of Te@O and the unusual increases and the obvious differences of the mobility of the electrons and holes are observed.